Combined Algorithm-Based Adaptations of Insulin Dose and Carbohydrate Intake During Exercise in Children With Type 1 Diabetes: Results From the CAR2DIAB Study - Lysy, Philippe Antoine; Absil, Hélène; Gasser, Emy; Boughaleb, Hasnae; Barrea, Thierry; Moniotte, Stéphane (Frontiers in Endocrinology, 2021)
OBJECTIVES: To evaluate the evolution of subcutaneous glucose during two sessions of monitored aerobic exercise in children or adolescents with type 1 diabetes after adaptation of insulin doses and carbohydrate intake according to a combined algorithm. METHODS: Twelve patients with type 1 diabetes (15.1 ± 2 years; diabetes duration: 9.5 ± 3.1 years) performed two series of exercise sessions after cardiac evaluation. The first series (TE#1) consisted in a monitored exercise of moderate to vigorous intensity coupled with a bout of maximum effort. The second series of exercises (TE#2) was carried out in real life during exercises categorized and monitored by connected watches. TE#2 sessions were performed after adaptation of insulin doses and fast-acting carbohydrates according to decision algorithms. RESULTS: Patients did not experience episodes of severe hypoglycemia, symptomatic hyperglycemia or hyperglycemia associated with ketosis. Analysis of CGM data (15h) during TE#2 sessions revealed an overall improvement in glycemic average [± standard deviation] (104 ± 14 mg/dL vs 122 ± 17 mg/dL during TE#1; P<0.001), associated with a decrease in proportion of hyperglycemia in periods ranging from 4h to 15h after performing the exercises. The proportion of hypoglycemia was not changed, except during the TE#2 +4-8h period, where a significant increase in hypoglycemia <60 mg/dL was observed (25 vs 6.2%; P=0.04), yet without concurrent complications. CONCLUSION: In our pediatric series, the application of algorithmic adaptations of insulin doses and carbohydrate intake has globally improved glycemic control during 15h after real-time exercises performed by children and adolescents with type 1 diabetes.